Cannabidiol industrial hemp growth, biomass, and temporal cannabinoids accumulation under different planting dates in southern Florida. Issue 1 (22nd March 2023) - Chiluwal, Anuj; Sandhu, Saroop S.; Sandhu, Hardev; Irey, Mike; Johns, Flint; Sanchez, Richard
Abstract: Due to limited information, identifying suitable cannabidiol (CBD) dominant industrial hemp ( Cannabis sativa L.) cultivars and optimal planting date are critical for hemp commercialization for CBD production in Florida. Two field trials were conducted with seven cultivars planted on three different dates from late April to late June. The cultivars were received from two different suppliers (Kentucky and Colorado) representing their adaptation. Plant growth parameters such as plant height and green canopy cover were recorded at 2−3 weeks intervals during crop growth. Temporal CBD and Δ‐9‐tetrahydrocannabinol (THC) concentrations in developing flowers were analyzed weekly beginning two weeks after flowering until maturity. The final floral biomass yield was measured at harvest. CBD and THC concentration curve over crop growing season varied among the tested cultivars. High positive correlations between CBD and THC concentrations ( R 2  = 0.88−0.98) were observed in all cultivars. This resulted in similar CBD/THC ratios across all planting conditions. Earlier planting resulted in higher CBD, THC, and floral biomass yield in a few cultivars, with no significant effect in most cultivars. Cultivars adapted in Kentucky performed better compared to Colorado in floral biomass and CBD yield. However, THC concentrations in the cultivars adapted in Kentucky mostly exceeded the acceptable legal threshold (0.3% THC) at harvest. Results indicate cultivar performance was affected more by genetics compared to planting date. Screening more cultivars adapted to regions of similar latitudes and environmental conditions is necessary to identify suitable hemp cultivars for Florida or similar climatic conditions. Core Ideas: Identifying suitable cultivars and optimal planting date is critical for hemp commercialization. Cultivar performance was largely affected by genetics compared to planting date. Cultivars adapted in Kentucky performed better compared with those adapted in Colorado in southern Florida. Suitable cultivars with THC level below the limit remain the major challenge in southern Florida. CBD and THC were positively correlated in all the studied cultivars.